Accounting for shifts in the frequency of suitable environments when testing for niche overlap. Issue 1 (1st December 2014) - Godsoe, William; Case, Bradley S.; Travis, Justin
Summary Organismal biologists need to detect and anticipate the effects of niche evolution. An increasing number of studies use information on changes in species' distribution to test for niche evolution. Typically, these studies will test to see whether the range of environments occupied by a species is similar in each biogeographic region. Niche evolution can change the occurrence probability (the frequency with which we observe a species) rather than the range of environments occupied. Using simulation, we test whether 13 previously implemented methods, and a novel approach (Expected Shared Presences), can identify shifts in occurrence probability. We show that even the best previously implemented methods detect shifts in the range of environments occupied, but provide poor inferences for shifts in occurrence probability. The expected shared presences approach provides a strong estimate of niche evolution due to shifts in niche overlap and shifts in occurrence probability. This work indicates that previous studies may have missed a substantial source of niche evolution. We argue that rigorous tests of niche overlap must account for shifts in both the range of environments occupied and the frequency of suitable environments.